Membrane-lipid therapy in operation: the HSP co-inducer BGP-15 activates stress signal transduction pathways by remodeling plasma membrane rafts. - Imre Gombos; Tim Crul; Stefano Piotto; Burcin Güngör; Zsolt Török; Gábor Balogh; Mária Péter; J Peter Slotte; Federica Campana; Ana-Maria Pilbat; Akos Hunya; Noémi Tóth; et al. (PLoS ONE)
Aging and pathophysiological conditions are linked to membrane changes which modulate membrane-controlled molecular switches, causing dysregulated heat shock protein (HSP) expression. HSP co-inducer hydroxylamines such as BGP-15 provide advanced therapeutic candidates for many diseases since they preferentially affect stressed cells and are unlikely have major side effects. In the present study in vitro molecular dynamic simulation, experiments with lipid monolayers and in vivo ultrasensitive fluorescence microscopy showed that BGP-15 alters the organization of cholesterol-rich membrane domains. Imaging of nanoscopic long-lived platforms using the raft marker glycosylphosphatidylinositol-anchored monomeric green fluorescent protein diffusing in the live Chinese hamster ovary (CHO) cell plasma membrane demonstrated that BGP-15 prevents the transient structural disintegration of rafts induced by fever-type heat stress. Moreover, BGP-15 was able to remodel cholesterol-enriched lipid platforms reminiscent of those observed earlier following non-lethal heat priming or membrane stress, and were shown to be obligate for the generation and transmission of stress signals. BGP-15 activation of HSP expression in B16-F10 mouse melanoma cells involves the Rac1 signaling cascade in accordance with the previous observation that cholesterol affects the targeting of Rac1 to membranes. Finally, in a human embryonic kidney cell line we demonstrate that BGP-15 is able to inhibit the rapid heat shock factor 1 (HSF1) acetylation monitored during the early phase of heat stress, thereby promoting a prolonged duration of HSF1 binding to heat shock elements. Taken together, our results indicate that BGP-15 has the potential to become a new class of pharmaceuticals for use in 'membrane-lipid therapy' to combat many various protein-misfolding diseases associated with aging.